Health Counseling on Breast Care for Pregnant Women at the Maternal and Child Health Polyclinic Aliyah 2 Kendari: Penyuluhan Kesehatan Tentang Perawatan Payudara Pada Ibu Hamil di Poliklinik KIA Aliyah 2 Kendari - Haryati Haryati; Saida Saida; Sukurni Sukurni; La Ode Alifariki (Yayasan Ahmar Cendekia Indonesia, 2022)
Exclusive breastfeeding is very beneficial for babies and mothers, for the smooth process of breastfeeding, it is very important for mothers to take care of their breasts after the delivery process. Health education activities and breast care assistance for postpartum women at the KIA ANLIYAH Kendari Polyclinic aim to increase the knowledge of pregnant women about breast care for pregnant and postpartum women. Breast care during childbirth is an important part that must be considered in breastfeeding. This community service is carried out by providing information about breast care and assistance on how to do breast care with a total of 10 participants. This community service uses communicative technique methods with three approaches, namely lectures, demonstrations, questions and answers and discussions. The results of breast care counseling are very useful for increasing the knowledge and skills of pregnant women. The results of the evaluation during the activity process were found that pregnant women had understood and knew how to do good and correct breast care. With this health education, it is expected to be able to increase the knowledge and skills of breastfeeding mothers about breast care and how to do breast care so that they can breastfeed and do not experience interference in the breastfeeding process so that the exclusive breastfeeding program can be achieved. Abstrak Pemberian ASI eksklusif sangat bermanfaat bagi bayi dan ibu, demi kelancaran proses menyusui, sangat penting bagi ibu melakukan perawatan payudara setelah proses persalinan. Kegiatan edukasi kesehatan dan pendampingan perawatan payudara pada ibu nifas di Poliklinik KIA ANLIYAH Kendari bertujuan meningkatkan pengetahuan ibu hamil tentang perawatan payudara pada ibu hamil dan nifas. Perawatan payudara selama persalinan adalah salah satu bagian penting yang harus diperhatikan dalam pemberian air susu ibu (ASI). Pengabdian kepada masyarakat ini dilakukan dengan cara memberikan informasi tentang perawatan payudara dan pendampingan cara melakukan perawatan payudara dengan jumlah peserta sebanyak 10 orang. Pengabdian masyarakat ini menggunakan metode teknik komunikatif dengan tiga pendekatan yaitu ceramah, demonstrasi, tanya jawab dan diskusi. Hasil dari penyuluhan perawatan payudara sangat bermanfaat untuk meningkatkan pengetahuan dan keterampilan ibu hamil. Hasil evaluasi selama proses kegiatan berlangsung didapatkan ibu hamil telah paham dan tahu bagaimana cara melakukan perawatan payudara yang baik dan benar. Dengan adanya edukasi kesehatan ini, diharapkan mampu meningkatkan pengetahuan dan keterampilan ibu menyusui tentang perawatan payudara dan cara melakukan perawatan payudara agar dapat menyusui dan tidak mengalami gangguan dalam proses menyusui sehingga program ASI eksklusif dapat tercapai.